2015
DOI: 10.1055/s-0034-1392481
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic dilation with a shape-measuring balloon in idiopathic achalasia: a feasibility study

Abstract: Background and aim: Pneumatic dilation is a commonly used treatment in achalasia. Recent studies have shown that esophageal distensibility measurements can be used to assess the effect of dilation and possibly the risk of perforation. A new hydraulic dilation balloon allows visualization of the shape of the balloon in vivo and measurement of distensibility during dilation. We aimed to evaluate the technical feasibility of a 30-mm shape-measuring hydraulic dilation balloon for the treatment of achalasia. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 17 publications
0
20
0
4
Order By: Relevance
“…Pneumatic dilation is performed with a noncompliant, cylindrical balloon (30 mm, 35 mm or 40 mm in diameter) positioned across the LES with fluoroscopic guidance and inflated using a handheld manometer. A study published in 2015 described a modification of this technique, with the introduction of a 30 mm diameter hydraulic dilator used in conjunction with FLIP technology and not requiring concomitant fluoroscopy 55 . The standard surgical alternative to pneumatic dilation is a LHM, in which the circular muscle fibres of the LES are surgically divided.…”
Section: Lhm and Pneumatic Dilationmentioning
confidence: 99%
“…Pneumatic dilation is performed with a noncompliant, cylindrical balloon (30 mm, 35 mm or 40 mm in diameter) positioned across the LES with fluoroscopic guidance and inflated using a handheld manometer. A study published in 2015 described a modification of this technique, with the introduction of a 30 mm diameter hydraulic dilator used in conjunction with FLIP technology and not requiring concomitant fluoroscopy 55 . The standard surgical alternative to pneumatic dilation is a LHM, in which the circular muscle fibres of the LES are surgically divided.…”
Section: Lhm and Pneumatic Dilationmentioning
confidence: 99%
“…There is no intra-bag pressure sensor included with the dilation balloons and thus, the diameter alone is utilized to target and follow dilation effect 22 . A recent study demonstrated the feasibility and clinical effectiveness of using the Eso-FLIP™ achalasia hydraulic dilation balloon (maximal diameter of 30-mm) 22 . As the EGJ can be identified with a waist on the real-time display to position the balloon, this device may allow for achalasia dilation to be performed without the concurrent use of fluoroscopy.…”
Section: Achalasiamentioning
confidence: 99%
“…We recently also reported the results of the first human study in newly diagnosed idiopathic achalasia patients [16]. In this pilot study, 10 patients were dilated twice with a 30 mm balloon, with a follow-up of 3 months.…”
Section: Initial Experiencementioning
confidence: 99%
“…This requires the development of new outcome data for typical pre-and postdilation pressures as measured with the dilation balloon in achalasia patients. As with EndoFLIP measurements, we used a balloon inflation volume of 30 mL for pre-and postdilation measurements in a feasibility study [16]. This volume produces a distending pressure of approximately 70 mmHg, whereas with EndoFLIP the same inflation volume produces a pressure of approximately 15 mmHg, the difference being the result of a greater balloon stiffness of the dilation balloon [7,16].…”
Section: Egj Distensibilitymentioning
confidence: 99%
See 1 more Smart Citation